The relationship of foreign direct investment with macroeconomic indicators towards economic growth in Malaysia/ Noorshila Ramly - Ramly, Noorshila (Faculty of Business Management, 2017)
To enhance the economic growth in Malaysia, foreign direct investment is a vital indicator. It was identified that foreign direct investment as a medium to acquire skills, knowledge, technologies and to internationalize business and at the same time to reduce debts. Though, in 2009, foreign direct investments into Malaysia had drop as much as 81.13 percent (Tanggapan, Geetha, Mohidin, & Vincent, 2011). This research paper is done to study about empirical question whether there is a relationship between gross domestic product, gross capital formation, inflation rate, and exchange rate with FDI that will react to enhance economic growth in Malaysia. Meanwhile, the objective of this study is to examine relationship among independent variables with the dependent variable. This study used annual time series data from 1981 to 2015 and Multiple Linear Regression analysis is applied to study the relationship between a dependent variable with independent variables. Empirical results show that gross capital formation and the inflation rate have significantly and positively relationship with Malaysia FDI inflows. While for gross domestic product and exchange rate, after the first differencing regression analysis, the result shows that these two variables do not have a significant relationship with FDI inflows of Malaysia, so these two variables were dropped from the model.